Communicative activities in the development of oral competence in Ecuadorian students compared to the Cambridge Key Exam - Calles-Jiménez, Romel Francisco; Paredes-Peralta, Diana Casandra; Aguirre-Alarcón, Carlos Alberto; Camacho-Oleas, María Eugenia (Revista de Ciencias Sociales, 2024)
The development of skills for oral communication in English is a necessity in today's society, given the importance that the use of this second language has acquired, both for academic training and for development in the workplace. Thus, the objective of this article is to demonstrate the impact generated on the development of oral competence at level A2 by the implementation of communicative activities in students candidates to take the international KEY test. The method included surveys to the group of participants from the High Challenge Language Institute in Riobamba, Ecuador. The results show that, regarding the oral competence and performance of former candidates who have taken the KEY international exam, the majority of students had difficulties with some sub-skills during this test and in their performance in classes; It was observed that carrying out these types of activities helps to improve the students' oral expression skills, even more so if they are carried out in an enjoyable and motivating way. It is concluded that the lack of significant practice during the development of the A2 level preparation course at High Challenge Language Institute affects the oral competence of the students.